Hong Kong Higher Education: A Turning Point? - Altbach, Philip G.; Postiglione, Gerard A. (International Higher Education, 2021)
Hong Kong’s universities have faced unprecedented challenges in the past year. Continuing social unrest concerning Hong Kong’s future culminated by the imposition by Mainland China of a security law curtailing much of the territory’s autonomy, profoundly shaking the universities as well as society. While it is too early to fully analyze the implications, Hong Kong’s universities might lose some of their international attractiveness and internal autonomy. Academic freedom is also called into question.